2017
DOI: 10.1021/acsami.7b12857
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Catalyst Residue Inhibition of the Functionalization of Single-Walled Carbon Nanotubes via the Billups–Birch Reduction

Abstract: The Billups-Birch Reduction chemistry has been shown to functionalize single-walled carbon nanotubes (SWCNTs) without damaging the sidewalls, but has challenges in scalability. Currently published work uses a large mole ratio of Li to carbon atoms in the SWCNT (Li:C) to account for lithium amide formation, however this increases the cost and hazard of the reaction. We report here the systematic understanding of the effect of various parameters on the extent of functionalization using resonant Raman spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…Thermogravimetric analysis (TGA, Figure 5) corroborated the results from EDS elemental analysis, with a final residue of 30 wt% and 18.4 wt% for the Rice University and NoPo HiPco samples, respectively. Given that the TGA was performed in air, these numbers account for the formation of iron oxides during heating [17,22], and the actual iron content in both samples are on the order of 21 wt% and 12.9 wt%, respectively, which is in good agreement with the EDS analysis ( Table 1). The nature of the weight loss plot for the two samples was also different, which also helps describe the carbon content in the samples.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Thermogravimetric analysis (TGA, Figure 5) corroborated the results from EDS elemental analysis, with a final residue of 30 wt% and 18.4 wt% for the Rice University and NoPo HiPco samples, respectively. Given that the TGA was performed in air, these numbers account for the formation of iron oxides during heating [17,22], and the actual iron content in both samples are on the order of 21 wt% and 12.9 wt%, respectively, which is in good agreement with the EDS analysis ( Table 1). The nature of the weight loss plot for the two samples was also different, which also helps describe the carbon content in the samples.…”
Section: Resultssupporting
confidence: 71%
“…We have previously reported that in order for A common figure of merit I G /I D (degree of order) was employed for the purposes of evaluating the defect density across different diameters [23]. We have previously reported that in order for meaningful I G /I D values, a number of measurements need to be made across a sample [17]. Table 2 gives the I G /I D value (with associated error) for both samples as a function of the excitation wavelength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Average EDS analysis of 4 aliquots taken from a large batch of SWCNTs. Each EDS analysis was taken of 4 areas giving the standard deviation showed defect sites [19,20]. Figure S3 (see ESM) shows representative Raman spectra (633 nm) for the four aliquots.…”
Section: Resulting Nanomaterials Aliquot Characterizationmentioning
confidence: 99%
“…Despite the potential application of both single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs) for a broad range of research and commercial fields extending from electronics to medicine [1,2], their purity is of paramount importance with many of the end-uses [3]. As a result, we have, among other things, concentrated much of our research efforts in developing purification methods to remove amorphous carbon, catalyst residue and defects [4][5][6]. Conversely, one of the most commonly raised value enhancements of materials by CNTs is the modification of elastomer properties [7], where purity can actually be detrimental in some cases.…”
Section: Introductionmentioning
confidence: 99%